The Plasmodium CSP repeats have elastic properties with a critical role in sporozoite motility - Balaban, Amanda; Kanatani, Sachie; Mitra, Jaba; Gregory, Jason; Vartak, Natasha; Sinnis-Bourozikas, Ariadne; Frischknecht, Friedrich; Ha, Taekjip; Sinnis, Photini (The EMBO journal, 2025)
The Plasmodium circumsporozoite protein (CSP) is the major surface protein of the sporozoite, the infective stage of the malaria parasite. The central repeat region of CSP is the primary immunological target of the sporozoite stage, yet little is known about its structure or function. Here, we show that sporozoite mutants with truncated or scrambled CSP repeats exhibit impaired motility due to altered adhesion site formation and dynamics. Since CSP forms the environment in which the thrombospondin-related anonymous protein (TRAP)-containing adhesion sites assemble, our data suggest that the dense CSP coat is altered in the repeat mutants, affecting adhesion site formation. We hypothesized that this role depends on the biophysical properties of the repeats, and used single-molecule fluorescence-force spectroscopy to test this hypothesis. Our results indicate that the CSP repeats behave like a stiff, linear spring with elastic properties that depend on its length and are lost when the repeats are scrambled. These data provide evidence for a functional role of the CSP repeat region during Plasmodium infection and motility.
Gesehen am 18.02.2026